Literatur Review: Agenda Kebijakan setelah Permendikbudristek No 30 Tahun 2021 - Abdurrahman Arif; Arif Rahman Hakim (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2023)
Permendikbud No 30 of 2021 is not a point for sexual violence in the higher education environment. Socialization is carried out in limited circles. Information regarding the number of complaints could not be found. This research aims to develop the PPKS agenda after the Permendikbud. Descriptive qualitative method is used to explain the formulation of the problem with the research source being secondary data, namely the study of journal articles and regulations related to this research. Validation of the validity of the data in this study using triangulation. This study uses the theory of setting the policy agenda, namely problem currents, policy currents and political currents. The results of this study are that the target of socialization is not comprehensive both in number and group (problem), the flow of reporting on survivors is available but the facilities are not yet (policy) and the leader determines how a policy is implemented (politics)